PP.30.39: HIGH DISCONTINUATION RATE OF ALISKIREN FOLLOWING ANTIBIOTIC THERAPY IN HYPERTENSIVE PATIENTS. (June 2015) - Kassi, M.; Mccallum, L.; Muir, S.; Touyz, R.M.; Dominiczak, A.F.; Padmanabhan, S.
Abstract : Objective: Antihypertensive drugs and antibiotics are the most commonly prescribed drugs in clinical practice and there is evidence of serious drug interactions between specific drug combinations. However, it is unclear if minor drug-drug interaction may lead to changes in antihypertensive drug adherence. We investigated whether antibiotic therapy results in discontinuation of specific antihypertensive drugs. Design and method: Electronic linkage data of 10, 090 hypertensive patients who attended the Glasgow BP clinic between 2006 and 2009 were analysed. The number of antihypertensive refill prescriptions over 12 months before and after antibiotic therapy was used to calculate drug discontinuation rates. We excluded the immediate 30 days post antibiotic therapy to avoid any acute effects due to the infection that instigated the antibiotic therapy. The discontinuation rates of all pairs of antihypertensive drugs were compared for different antibiotic exposures using an exact rate ratio test, assuming Poisson distribution. Results: Amoxicillin was the most commonly prescribed antibiotic among the ten antibiotics studied during the 4 year study period. The average age of the patients was 62.2(15.3) years with 62% females. The figure shows the risk of discontinuation of the antihypertensive drug on the abscissa relative to the drug on the ordinate. Aliskiren was associated with the highest discontinuation rate when compared to all other antihypertensive drugs following any antibiotic therapy. The highest rate of discontinuation for Aliskiren was seen after metronidazole therapy. Vasodilators were the next group with high discontinuation rate post-antibiotics. ACEI was associated with an 80% discontinuation rate compared to ARB following doxycycline suggesting doxycycline was possibly prescribed for ACEI induced cough. Figure. No caption available. Conclusions: Exact reasons for discontinuation of aliskiren and vasodilators after antibiotic therapy are unclear but discontinuation needs to be monitored and addressed promptly to ensure adequate BP control.